Faktor – Faktor Yang Mempengaruhi Minat Belajar Siswa di Masa Pandem - Putrina Mesra; Eko Kuntarto; Faizal C han (Peneliti.net, 2021)
This study aims to determine what factors influence student interest in learning during the pandemic at SD Negeri 13/1 Muara Bulian. The approach in this research is qualitative research, the type of research is case study. This research was conducted at SD Negeri 13/1 Muara Bulian. The data in this study are descriptions obtained through observation and interviews with informants regarding the factors that influence student interest in learning during the pandemic. Respondents in this study were teachers, students and parents of grade I B students of SD Negeri 13/I Muara Bulian. Based on the results of this study, it is shown that: (1) Internal factors that influence student interest in learning during the pandemic include a sense of pleasure in participating in the learning process. Support from students' parents is one of the motivations outside of students. (2) External factors that affect student learning interest during the pandemic include infrastructure. Facilities and infrastructure that support learning process activities include internet network access, mobile phones to support teaching and learning activities, and other student stationery. Parents provide facilities for children's learning, so that learning activities can run and children are more enthusiastic in learning, which will make it easier for children to master the learning material.